2023
DOI: 10.1002/mma.9177
|View full text |Cite
|
Sign up to set email alerts
|

𝒼‐asymptotically 𝓌‐periodic mild solutions for noninstantaneous impulsive integro‐differential equations with state‐dependent delay

Abstract: A kind of nonlinear noninstantaneous impulsive equation with state‐dependent delay is studied here. By utilizing suitable fixed point theorem and the theory of semigroup in Banach space, the uniqueness and existence results of  scriptS$$ \mathcal{S} $$‐asymptotically  w$$ w $$‐periodic mild solutions are obtained, respectively. In the end, two examples are presented to demonstrate the validity of the obtained results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Intensive studies over the years revealed that mathematical modeling and simulation can play a significant role in understanding the reasons for diverse infectious diseases, thereby predicting the possible cure. It is needless to say that mathematical modeling of VL has a rich history wherein numerous reports exist on the classical, fractional, statistical, machine learning models, and so forth [1][2][3][4][5][6][7][8][9]. In addition, it was acknowledged that the fractional calculus can offer deep insights into the dynamics of VL, leading to more accurate model and effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies over the years revealed that mathematical modeling and simulation can play a significant role in understanding the reasons for diverse infectious diseases, thereby predicting the possible cure. It is needless to say that mathematical modeling of VL has a rich history wherein numerous reports exist on the classical, fractional, statistical, machine learning models, and so forth [1][2][3][4][5][6][7][8][9]. In addition, it was acknowledged that the fractional calculus can offer deep insights into the dynamics of VL, leading to more accurate model and effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%